Incidence, Risk Factors, Risk Assessment Model and Compliance of Patients on Anticoagulants for Asymptomatic Venous Thromboembolism in Nononcological Urological Inpatients - Li, Kaixuan; Zhu, Quan; Li, Haozhen; Wu, Ziqiang; Han, Feng; Tang, Zhengyan; Wang, Zhao (Urology Journal, 2022)
Purpose: To study the incidence, risk factors for developing asymptomatic venous thromboembolism and the compliance of patients on anticoagulants for asymptomatic venous thromboembolism (VTE) in nononcological urological medium-high risk inpatients, and build a risk assessment model (RAM) for early screening for asymptomatic VTE. Materials and Methods: We conducted a retrospective analysis of 573 inpatients admitted to a nononcological urological ward of a tertiary hospital in China from January 1, 2017, to June 30, 2019. Data were collected using the electronic medical record system, and patients underwent a follow-up by phone 6 months after discharge. Results: Among the 573 medium-high risk inpatients, 73 (15.4%) were diagnosed with VTE, including 20 (4.2%) symptomatic and 53 (11.2%) asymptomatic. Prior history of VTE, a history of anticoagulants or antiplatelet agents before admission, and D-dimer ≥ 1 were the potential risk factors identified for asymptomatic VTE. Patients with poor awareness of VTE and its dangers, and patients who lived more than 1 hour away from the hospital had a high probability of poor compliance with anticoagulation therapy after discharge. Using D-dimer (1.785 μg/ml), we built a RAM for the early diagnosis of asymptomatic VTE. Conclusion: We found that patients with urinary nontumor VTE had low compliance with anticoagulation therapy after discharge. The key factors for determining asymptomatic VTE in nononcological urological inpatients included prior history of VTE, a history of taking anticoagulants or anti-platelet agents before admission, and D-dimer ≥ 1. Furthermore, we found that the threshold of D-dimer should be elevated to 1.785 μg/ml to predict asymptomatic VTE.